1982
DOI: 10.1271/bbb1961.46.2183
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of 10-hydroxypheophorbide a as a photosensitizing pigment from alcohol-treated Chlorella cells.

Abstract: A new pigment causing intense photosensitivity in rats was isolated from alcohol-treated Chlorella cells and identified as 10-hydroxypheophorbide a by chemical analysis, chromatography, and visible, infrared, nuclear magnetic resonance and mass spectroscopy methods. Whenrats administered orally with this pigment were exposed immediately to the visible light, signs of the intense photosensitivity including death occurred after a few hours ofphotoirradiation. The photosensitizing activity of this pigment in rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The reaction mixture was evaporated with a stream of argon, the residue dissolved in ethyl acetate, washed with H,O, dried over Na,SO, and evaporated to dryness. The absorption spectrum showed a typical pheophytin b spectrum, thin-layer chromatography according to Endo et al (1982) showed the complete saponification of pheophytin b to pheophorbide 6. Zinc was inserted by the standard method described by Helfrich et al (1994) using a mixture of zinc acetate and cadmium acetate in CH,Cl,/methanol.…”
Section: Methodsmentioning
confidence: 97%
“…The reaction mixture was evaporated with a stream of argon, the residue dissolved in ethyl acetate, washed with H,O, dried over Na,SO, and evaporated to dryness. The absorption spectrum showed a typical pheophytin b spectrum, thin-layer chromatography according to Endo et al (1982) showed the complete saponification of pheophytin b to pheophorbide 6. Zinc was inserted by the standard method described by Helfrich et al (1994) using a mixture of zinc acetate and cadmium acetate in CH,Cl,/methanol.…”
Section: Methodsmentioning
confidence: 97%
“…Endo et al (29) have demonstrated that 13 2 -hydroxypheophorbide a and some relative Chl allomers isolated from Chlorella cells are photosensitizers but have made no mention of 13 2 -hydroxychlorophyll a. One of the most important findings of this work is that our data clearly indicate RWH-21-induced 13 2 -hydroxychlorophyll a has the potential to cause photoinduced damage in cultured tobacco cells that, in turn, suggests that this Chl allomer may be a photosensitizer.…”
Section: Discussionmentioning
confidence: 50%
“…marinoi ( Table 1 ). Compound ( 3 ) m/z 247.1707 [M+H] - , C 16 H 24 O 2 (Δppm = 0.5) was dereplicated as 10-phenyldecanoic acid [ 36 ]; ( 4 ) m/z 489.3075 [M+H] - , C 25 H 46 O 9 (Δppm = 3.0), as a derivative of glycerol 1-(9-hexadecenoate) [ 37 ]; ( 5 ) m/z 649.3427 [M+H] - , C 34 H 46 N 6 O 7 (Δppm = 10.8), as aeruginosin KT650 [ 38 ]; ( 6 ) m/z 249.1869 [M+H] - , C 16 H 26 O 2 (Δppm = 3.7), as 8,11,14-hexadecatrienoic acid or 6,10,14-hexadecatrienoic acid [ 39 ]; ( 7 ) m/z 552.2343 [M+H] - , C 26 H 47 IO 4 (Δppm = 1.5), as a iodolactone derivative [ 40 ]; ( 8 ) m/z 351.2533 [M+H] + , C 21 H 34 O 4 (Δppm = 2.3), as 9- O -methylconstanolactone B [ 41 ]; ( 9 ) m/z 329.2668 [M+H] + , C 19 H 36 O 4 (Δppm = 2.0), as ceratodictyol A or B [ 42 ]; ( 10 ) m/z 609.2734 [M+H] + , C 35 H 36 N 4 O 6 (Δppm = 4.5), as 10-hydroxyphaeophorbide A [ 43 ]; ( 11 ) m/z 313.2725 [M+H] + , C 19 H 36 O 3 (Δppm = 3.0), as tetrahydro-2-(1-hydroxy-9-nonenyl)-5-pentyl-3-furanol [ 44 ]; ( 12 ) m/z 285.2411 [M+H] + , C 17 H 32 O 3 (Δppm = 4.7), as tanikolide [ 45 ]; ( 13 ) m/z 303.2532 [M+H] + , C 17 H 34 O 4 (Δppm = 0.6), as secotanikolide [ 46 ]. Isomers were found for ( 7 ) at a retention time of 15.30 and 15.70 min, ( 9 ) at 17.45 and 18.01 min, ( 10 ) at 24.73 and 25.49 min, ( 11 ) at 21.14 and 21.94 min.…”
Section: Resultsmentioning
confidence: 99%